(untitled) (Journal of University of Babylon for Engineering Sciences, 2024)
Modern communication network advancement needs continuous research to develop various technologies relating to 5G and beyond. Since 5G is supposed to support many users with fast data transfer, the Multiple Access Scheme is one of the crucial features that has received the most attention from researchers. One major area of interest is the non-orthogonal multiple access (NOMA) scheme. One solution that shows promise in the NOMA scheme is sparse code multiple access (SCMA), which improves wireless communication’s multiuser capacity. This review explains the principle of the SCMA encoder and the mother constellation (MC) design. Further, studied different codebook (CB) designs based on QAM and discussed them using various important factors regarding BER, PAPR, and Euclidean distance ( ). The discussion shows that hypercube QAM is optimal for SCMA compared to others. Finally, the article also presents the opportunities and difficulties associated with SCMA codebook design in multiple criteria. Modern communication network advancement needs continuous research to develop various technologies relating to 5G and beyond. Since 5G is supposed to support many users with fast data transfer, the Multiple Access Scheme is one of the crucial features that has received the most attention from researchers. One major area of interest is the non-orthogonal multiple access (NOMA) scheme. One solution that shows promise in the NOMA scheme is sparse code multiple access (SCMA), which improves wireless communication’s multiuser capacity. This review explains the principle of the SCMA encoder and the mother constellation (MC) design. Further, studied different codebook (CB) designs based on QAM and discussed them using various important factors regarding BER, PAPR, and Euclidean distance ( ). The discussion shows that hypercube QAM is optimal for SCMA compared to others. Finally, the article also presents the opportunities and difficulties associated with SCMA codebook design in multiple criteria.